Tingkat Pengetahuan Permainan Tradisional Siswa Kelas V Sekolah Dasar Negeri di Kota Semarang Tahun 2022 - Anggoro, Rizal Budi; Nurharsono, Tri (Indonesian Journal for Physical Education and Sport, 2023)
Nowadays, traditional games are rarely played in the community. The purpose of this study was to determine the level of knowledge of fifth grade elementary school students on traditional games. The research method uses a quantitative descriptive survey research design. The sample collection technique used cluster random sampling, namely fifth grade students at SD Negeri Tanjung Mas, SD Negeri Kalipancur 02 and SD Negeri Pakintelan 02. The total sample was 88 students. The instrument uses a questionnaire. Data analysis techniques using quantitative descriptive with percentages. The results of this study show that the level of knowledge of traditional games for fifth grade students at SD Negeri Tanjung Mas is in the medium category (35.14%), SD Negeri Kalipancur 02 is in the high category (41.38%) and SD Negeri Pakintelan 02 is in the high category (36.36%). . The conclusion of this study is that the level of knowledge of traditional games for fifth grade students at SD Negeri Tanjung Mas, SD Negeri Kalipancur 02 and SD Negeri Pakintelan 02 are in the very low category of 6 students (6.82%), in the low category of 17 students (19.32). %), the medium category is 29 students (32.95%), the high category is 30 students (34.09%) and the very high category is 6 students (6.82%).